Assessment of oxidative stability and physicochemical, microbiological, and sensory properties of beef patties formulated with baobab seed (Adansonia digitata) extract. (April 2020) - Al-Juhaimi, FahadY.; Babtain, Ibrahim A.; Mohamed Ahmed, Isam A.; Alsawmahi, Omer N.; Ghafoor, Kashif; Adiamo, Oladipupo Q.; Babiker, Elfadil E.
Abstract: The present study was conducted to evaluate the oxidative stability and the physicochemical, microbiological, and sensory properties of beef patties formulated with different concentrations (1%, 2%, and 3%) of baobab seed extract (BSE) during storage at 4 °C. The BSE contained a considerable number of phenolic compounds and exhibited antioxidant and antimicrobial activities (both on gram-positive and negative bacteria). The chemical composition of the patties was not altered by BSE treatment. However, the addition of 2% and 3% BSE improved the lipid stability and enhanced the antioxidant activity of beef patties during storage. Furthermore, the shelf-life of patties formulated with 2% and 3% of BSE increased from 7 days (control group) to 21 days. Moreover, the patties formulated with BSE received overall acceptability in the sensory evaluation. In conclusion, the inclusion of 2% or 3% BSE could be recommended as a natural antioxidant additive in beef patties. Highlights: The effect of baobab seed extract (BSE) on storage stability and quality of beef patties was assessed. This is the first report on using BSE as a preservative in meat patties. BSE showed good antioxidant and antibacterial activities. BSE improved the storage stability, antioxidants and cooking properties of the patties. This study could add commercial value to the seeds of baobab.